2011
DOI: 10.1016/j.jns.2011.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological responses to stereotactic focal irradiation of the adult rodent hippocampus

Abstract: Radiation effectively treats brain tumors and other pathologies but dose and treatment plans are limited by normal tissue injury, a major cause of morbidity in survivors. Clinically significant normal tissue injury can occur even with therapies that target pathological tissue and limit out-of-target irradiation. Elucidating the mechanisms underlying normal tissue injury is facilitated by studying the effects of focal irradiation and comparing irradiated and un-irradiated tissue in experimental animals. Young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…But such radiotherapeutic plans were also reported to have severe side effects, especially on neuro-cognition of memory and social understanding. Later studies 3 , 4 revealed that it was the radiation damage on hippocampus during radiotherapy that caused neuro-cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But such radiotherapeutic plans were also reported to have severe side effects, especially on neuro-cognition of memory and social understanding. Later studies 3 , 4 revealed that it was the radiation damage on hippocampus during radiotherapy that caused neuro-cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Yet this radiotherapeutic strategy was reported to present severe side effects of a decline in memory and social understanding after treatment 3 . And such neuro-cognitive dysfunction was later found out to be attributed to radiation damage on the hippocampus dentate gyrus caused by radiation treatment 4 . However, intensity modulated radiation therapy (IMRT) 5 , including Volumetric Modulated Arc Therapy (VMAT) 6 , 7 , has been widely used in NPC patients.…”
Section: Introductionmentioning
confidence: 99%